2014
DOI: 10.3349/ymj.2014.55.2.499
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Laryngeal Disease in South Korea: Data from the Korea National Health and Nutrition Examination Survey from 2008 to 2011

Abstract: PurposeThe aim of this study was to evaluate the prevalence of Benign Vocal Fold Lesion (polyp, cysts, nodules) and Leukoplakia in Korea.Materials and MethodsThe data from the 2008 to 2011 Korea National Health and Nutrition Examination Surveys, which were cross-sectional survey of the civilian noninstitutionalized population of South Korea. A survey team that included an otolaryngology residents, nurses, and interviewers moved with a mobile examination unit and performed laryngologic interviews and examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 18 publications
(20 reference statements)
0
24
2
Order By: Relevance
“…Two studies [3,7] reported psychogenic disorders occurring significantly more often in females, which cannot be confirmed by this study and the findings of Coyle et al [4]. Woo et al [8] reported no significant differences between males and females for the prevalence of nodules, cysts, polyps and leukoplakia. These differences are probably related to different inclusion/exclusion criteria, ethnical/cultural aspects and the fact that our research population was restricted to a treatment-seeking group.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Two studies [3,7] reported psychogenic disorders occurring significantly more often in females, which cannot be confirmed by this study and the findings of Coyle et al [4]. Woo et al [8] reported no significant differences between males and females for the prevalence of nodules, cysts, polyps and leukoplakia. These differences are probably related to different inclusion/exclusion criteria, ethnical/cultural aspects and the fact that our research population was restricted to a treatment-seeking group.…”
Section: Discussioncontrasting
confidence: 73%
“…Thirdly, population size and population distribution (children, adults, professionals) differ across studies and centers. In most studies, the enrolled subjects were limited to a population of a specific age or occupation group [8]. Data on the prevalence of dysphonia can be useful in estimating clinical needs and costs for a specific patient population.…”
Section: Introductionmentioning
confidence: 99%
“…They reflect the situation of a service and exclude individuals who do not seek treatment. An epidemiological recent study evaluated the prevalence of laryngeal diseases in South Korea, but did not mention specific data on voice disorders [24].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological information on prevalence of voice disorders helps to know the dimension of their effects on the communication skills and general health of the population, to estimate impact of expenses, to delineate the associate factors, and to develop early screening procedures to detect those at risk [21][22][23][24]. Therefore, the aim of the present review was to identify the prevalence of vocal disorders in elderly people in population-based studies.…”
Section: Introductionmentioning
confidence: 99%
“…1 From the 19,636 adult subjects who were interviewed and assessed with mobile laryngoscopy units, 385 were positive for abnormal findings, which corresponds with a 1.96% prevalence of organic laryngeal disease (not taking other laryngeal pathologies into account, eg, paralysis, muscle tension dysphonia, and spasmodic dysphonia). This finding highlights the demand for methods to comprehensively assess voice (pathology) at the initial stage and to track outcomes of specific voice prevention, education, and treatment programs.…”
Section: Introductionmentioning
confidence: 99%